Ehlers-Danlos syndrome: a case report - M. M. Umanets; O. V. Zborovska; O. E. Dorokhova; M. L. Kogan (Ukrainian Society of Ophthalmologists, 2022)
Background: Ehlers-Danlos syndrome (EDS) is a rare disease characterized by connective tissue dysplasia, and, consequently, structural changes in ocular tissues. To the best of our knowledge, only 3 cases of surgical treatment with vitrectomy for retinal detachment in EDS have been reported in the literature. Purpose: To review an approach to medical and surgical treatment for recurrent retinal detachment in a patient with EDS. Material and Methods: Data on the clinical condition of eyes, examination findings and outcomes of conservative and surgical treatment were reported. Results: Substantial remnants of the vitreous were found in the periphery during surgical re-examination of the vitreous cavity, and were as much as possible removed with a vitreous cutter. Trypan blue staining of the retina facilitated the removal of the epiretinal membrane covering the whole posterior pole, and the membrane was completely removed with forceps. Conclusion: We argue for a more differentiated approach to the examination and treatment of patients with Ehlers-Danlos syndrome, because connective tissue dysplasia may mimic another systemic autoimmune disease. Early treatment and adequate treatment strategy enable treatment success for especially severe cases.